Ischemia-Reperfusion Injury Reduces Kidney Folate Transporter Expression and Plasma Folate Levels - Yang, Cheng; Wijerathne, Charith U. B.; Tu, Guo-wei; Woo, Connie W. H.; Siow, Yaw L.; Madduma Hewage, Susara; Au-Yeung, Kathy K. W.; Zhu, Tongyu; O, Karmin (Frontiers in Immunology, 2021)
Acute or chronic kidney disease can cause micronutrient deficiency. Patients with end-stage renal disease, kidney transplantation or on dialysis have reduced circulating levels of folate, an essential B vitamin. However, the molecular mechanism is not well understood. Reabsorption of folate in renal proximal tubules through folate transporters is an important process to prevent urinary loss of folate. The present study investigated the impact of acute kidney injury (AKI) on folate transporter expression and the underlying mechanism. AKI was induced in Sprague-Dawley rats that were subjected to kidney ischemia (45min)-reperfusion (24h). Both male and female rats displayed kidney injury and low plasma folate levels compared with sham-operated rats. The plasma folate levels were inversely correlated to plasma creatinine levels. There was a significant increase in neutrophil gelatinase-associated lipocalin (NGAL) and IL-6 mRNA expression in the kidneys of rats with ischemia-reperfusion, indicating kidney injury and increased inflammatory cytokine expression. Ischemia-reperfusion decreased mRNA and protein expression of folate transporters including folate receptor 1 (FOLR1) and reduced folate carrier (RFC); and inhibited transcription factor Sp1/DNA binding activity in the kidneys. Simulated ischemia-reperfusion through hypoxia-reoxygenation or Sp1 siRNA transfection in human proximal tubular cells inhibited folate transporter expression and reduced intracellular folate levels. These results suggest that ischemia-reperfusion injury downregulates renal folate transporter expression and decreases folate uptake by tubular cells, which may contribute to low folate status in AKI. In conclusion, ischemia-reperfusion injury can downregulate Sp1 mediated-folate transporter expression in tubular cells, which may reduce folate reabsorption and lead to low folate status.